Impact of improved varieties on farmers income: Insight from lower Shivalik hills - ROY, PINAKI; HANSRA, B S; BURMAN, R ROY; ROY, T N; BHATTACHARYYA, SANGEETA; KUMAR, PRABHAT (The Indian Journal of Agricultural Sciences, 2021)
High yielding varieties of cereal crops were the major contributors to India’s Green Revolution in 1960s and till date these varieties have been largely contributing to India’s bread basket. Uttarakhand is primarily an agricultural state although its share in the country’s total area and production is negligible. In this paper the authors have attempted to measure the technical and economic efficiencies of improved varieties of paddy and wheat in lower Shivalik hills of Uttarakhand during 2017-20. Uttarakhand is primarily an agricultural state although its share in the country’s total area and production is negligible. Economic efficiencies of the varieties were measured by benefit-cost ratio (BCR) andnet return (NR). Technical efficiencies were measured by Box plot technique in R software. Kernal density plot was used to represent yield variation among the varieties. The findings revealed that PB 1121 paddy and HD 2967 wheat respectively were the best varieties in terms of technical efficiency (productivity) and economic efficiency (BCR andNet Return). Estimates of t-test also show the significant differences in BCR and net return between improved and local varieties. Thus, study shows that the positive impacts of improved varieties of the major crops have significantly contributed to productivity, farm income and livelihood in the lower Shivalik hills of Uttarakhand which, in turn, mayprovide prospective implications towards country’s total production and food security.